The potential and challenges of thin-film electrolyte and nanostructured electrode for yttria-stabilized zirconia-base anode-supported solid oxide fuel cells - Noh, Ho-Sung; Yoon, Kyung Joong; Kim, Byung-Kook; Je, Hae-June; Lee, Hae-Weon; Lee, Jong-Ho; Son, Ji-Won (ELSEVIER SCIENCE BV, 2014)
Thin-film electrolytes and nanostructured electrodes are essential components for lowering the operation temperature of solid oxide fuel cells (SOFCs); however, reliably implementing thin-film electrolytes and nano-structure electrodes over a realistic SOFC platform, such as a porous anode-support, has been extremely difficult. If these components can be created reliably and reproducibly on porous substrates as anode supports, a more precise assessment of their impact on realistic SOFCs would be possible. In this work, structurally sound thin-film and nano-structured SOFC components consisting of a nanocomposite NiO-yttria-stabilized zirconia (YSZ) anode interlayer, a thin YSZ and gadolinia-doped ceria (GDC) bi-layer electrolyte, and a nano-structure lanthanum strontium cobaltite (LSC)-base cathode, are sequentially fabricated on a porous NiO-YSZ anode support using thin-film technology. Using an optimized cell testing setup makes possible a more exact investigation of the potential and challenges of thin-film electrolyte and nanostructured electrode-based anode-supported SOFCs. Peak power densities obtained at 500 degrees C surpass 500 mW cm(-2), which is an unprecedented low-temperature performance for the YSZ-based anode-supported SOFC. It is found that this critical, low-temperature performance for the anode-supported SOFC depends more on the electrode performance than the resistance of the thin-film electrolyte during lower temperature operation. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: PULSED-LASER DEPOSITION; PERFORMANCE; SOFC; MEMBRANES; MICROSTRUCTURE; TEMPERATURE; FABRICATION; CATHODES; COMPOSITE; DIFFUSION